Investigation of Primary School Teachers’ Attitudes towards Science Topics: Adaptation of the Original Version of DAS Questionnaire to Czech Environment - Rusek, Martin; Bílková Metelková, Iva; Chytrý, Vlastimil; Žák, Vojtěch (Scientia in educatione, 2020)
Late exposition to science topics in enducation is considered one of the reasons of contemporary students’ negatve attitudes toward science and later their interest in future profession in science. Improvement of this state is closely connected to primary school teachers’ preparedness to teach science topics in a way they iniciate development of pupils’ positive attitudes. A substantial role play attitudes of the teachers themselves, as they can serve as indicators of a need of change in this field. The goal of this paper is to introduce a Czech version of the DAS (Dimensions of Attitude toward Science) scale which was designed to investigate primary school attitudes towards science topics and their teaching. The scale contains 28 items separated into seven subscales. The data gathered using this tool provide overall information about a respondent’s attitude, at the same time, enable to creat an “attitude profile” (high potential, promissing, indifferent, unwilling). Based on this information, it is possible to choose ways of individual teacher’s support. The original version of the research tool was first translated, piloted and further used in a research. Based on the results of the statistical analysis (Crombacg alpha = .704 for the whole scale), it is possible to consider the Czech version of the scale sufficiently reliable and applicable in further research, moreover with respect to the high reliability of particular subscales of the research instrument.